2019
DOI: 10.1371/journal.pbio.2006926
|View full text |Cite
|
Sign up to set email alerts
|

Differential and convergent utilization of autophagy components by positive-strand RNA viruses

Abstract: Many viruses interface with the autophagy pathway, a highly conserved process for recycling cellular components. For three viral infections in which autophagy constituents are proviral (poliovirus, dengue, and Zika), we developed a panel of knockouts (KOs) of autophagy-related genes to test which components of the canonical pathway are utilized. We discovered that each virus uses a distinct set of initiation components; however, all three viruses utilize autophagy-related gene 9 (ATG9), a lipid scavenging prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 110 publications
2
86
0
2
Order By: Relevance
“…However, among the 30 odd autophagy-related genes, the functional contribution of the individual components in virus infection is far from clear. A recent targeted CRISPR/Cas9 screen uncovered a fairly diverse range of involvement among autophagic components in three +RNA RNA virus infections -PV, DENV and ZIKV [29]. The authors reported that all three viruses employed multiple proteins of the autophagy pathway while bypassing others, and each virus used a unique set of initiation components.…”
Section: Subversion Of Autophagy By +Rna Virusesmentioning
confidence: 99%
“…However, among the 30 odd autophagy-related genes, the functional contribution of the individual components in virus infection is far from clear. A recent targeted CRISPR/Cas9 screen uncovered a fairly diverse range of involvement among autophagic components in three +RNA RNA virus infections -PV, DENV and ZIKV [29]. The authors reported that all three viruses employed multiple proteins of the autophagy pathway while bypassing others, and each virus used a unique set of initiation components.…”
Section: Subversion Of Autophagy By +Rna Virusesmentioning
confidence: 99%
“…Due to their complex composition and functions, virus factories could be contemplated as the living state of viruses . Two main pathways have been identified so far as being responsible for viral factory biogenesis: aggresome formation for DNA viruses and autophagy for RNA viruses (Abernathy et al, 2019;Jackson et al, 2005;Kajitani et al, 2013;Wileman, 2007). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they found that SQSTM1 was cleaved and digested in a non-canonical manner in poliovirus infected cells [97], similar to the aforementioned CVB3 infected cells [94]. However, Abernathy et al recently reported that depletion of autophagy-related protein 9 (ATG9), ULK1, FIP200 and LC3B undermined poliovirus replication, while knockout of VPS34, Beclin-1 and ATG5 did not affect viral production [99]. They further demonstrated that poliovirus recruited the non-lipid-bound form of LC3 to the remodeled membranes in GFP-LC3-G120A expressing cells, indicating that the canonical PE-linked LC3, an essential form in autophagosome formation, is not required for poliovirus replication [99].…”
Section: Poliovirusmentioning
confidence: 68%
“…Poliovirus has been reported to benefit from virus induced autophagy according to several research [5,[96][97][98][99]. Double-membrane autophagy-like vesicles can be observed in poliovirus infected COS-1 cells under electron microscopy [96].…”
Section: Poliovirusmentioning
confidence: 99%
See 1 more Smart Citation